Social Assistance Policies Amid the 2024 Presidential Election Contestation: An Islamic Political Economy Perspective - Suhirman, Suhirman; Mashilal, Mashilal; Sahala, Fika (Economica: Jurnal Ekonomi Islam, 2025)
This research examines the dual function of social aid in Indonesia as a social safety net and as a political tool for the upcoming 2024 Presidential Election. This research used Fairclough's model of critical discourse analysis through the policymaking process of social assistance programmes, including articles in the online media, social aid (PKH, BPNT, KIP, and others), and the dynamics of public opinion from January to June 2024. The analysis of the data showed that in election years, the social aid budgets are increased. The social assistance is therefore politically motivated. However, these programmes help to some extent reduce poverty and improve access to education and health. Because of the political motivation, the assistance programmes lose their main social purpose. From the perspective of the Islamic political economy, the social assistance programmes should be based on maṣlaḥah al-‘āmmah. The underlying principle is the equitable social welfare of the people and the politically unmotivated equitable social wealth. This research demands that these assistance programmes and services be legally and politically unmotivated, and social welfare programmes be legally focused on the redistribution and social justice of the people, be oriented to the long-term social welfare of politically and legally unmotivated social welfare programmes.